2009
DOI: 10.21608/jfds.2009.113448
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Characteristics of Some Fruit Juice Blends and Their Organoleptic Evaluations.

Abstract: This study was conducted to study the physico-chemical characteristics of some juices and the possibility of producing fortified and enhanced blended juices. Physico-evaluation showed that pumpkin juice contains 7.30 % T.S.S, 0.730 browning index, 1.83 centipoise/s for viscosity and 1.782 turbidity. Mango juice gave a higher score of viscosity being 3.22 centipoise/s,color value, turbidity and T.S.S% orange juice gave high score of pH 3.80. Concerning chemical analysis the data indicated that pumpkin juice con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The samples containing only apple juice are green (negative values of the color parameter a*) and the others have positive values for the parameter a*, which means red color. Negative values for the color parameter a* were reported also by Ghinea et al [ 54 ] between −0.96 and 0.05 for fresh apple juice, while for pomegranate juice, Tarantino et al [ 80 ] indicated values between 4.1 and 13.00, and for pumpkin juice, Allam et al [ 79 ] obtained a* = 6.68. The red color of pomegranate juice is due to natural monomeric anthocyanin pigments [ 98 , 99 ], the predominant being cyanidin-3,5-diglucoside and delphinidin-3,5-diglucoside according to Micó-Vicent et al [ 100 ].…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…The samples containing only apple juice are green (negative values of the color parameter a*) and the others have positive values for the parameter a*, which means red color. Negative values for the color parameter a* were reported also by Ghinea et al [ 54 ] between −0.96 and 0.05 for fresh apple juice, while for pomegranate juice, Tarantino et al [ 80 ] indicated values between 4.1 and 13.00, and for pumpkin juice, Allam et al [ 79 ] obtained a* = 6.68. The red color of pomegranate juice is due to natural monomeric anthocyanin pigments [ 98 , 99 ], the predominant being cyanidin-3,5-diglucoside and delphinidin-3,5-diglucoside according to Micó-Vicent et al [ 100 ].…”
Section: Resultsmentioning
confidence: 81%
“…Gil et al [ 75 ] determined a pH value of 3.31, while Rydzak et al [ 76 ] obtained pH values between 3.38 and 3.47. According to Kiskó and Roller [ 77 ], the pH of fresh apple juice can vary between 2.9 and 4.5, while pumpkin juice can have a pH between 5.34 [ 78 ] and 5.86 [ 79 ], and pomegranate juice between 2.8 and 3.6 [ 80 ] and even 3.9 [ 81 ]. The values of pH for fresh apple and pumpkin juice range from 4.36 to 4.47, which means that adding the pumpkin juice leads to an increase in pH values (are obtained juices with very little acidity), while adding the pomegranate juice to apple juice leads to a decrease in pH values (3.79–3.86).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations